Urgensi Perguruan Tinggi dalam Pembentukan Karakter Bangsa - Mujiburrahman Mujiburrahman (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2016)
The Indonesian nation is being hit by a moral crisis. This is due to mistakes in both policy and operational levels in education, economics, politics and law. Educational institutions especially accused of failing to shape the character, moral and noble character of the students. This phenomenon seems to be the basis for universities to think, implement and develop the paradigm and character education system in line with the spirit of Islamic sharia values. Through Islamic education-based educational model that actualized in the process of education in total and comprehensive provide wide space and opportunity to shape the character and personality of children (students) in accordance with the demands of Islamic values. So in the end, the orientation and the ultimate goal of educational activities to realize the individual (Muslim person) and members of society (Muslim community) who have a high quality of faith, noble, character, knowledgeable and professional can be achieved.